ESTIMASI FUNGSI PRODUKSI DAN EFISIENSI ALOKASI SUMBERDAYA PETANI KEDELAI DI LOMBOK BARAT - Nufus, Nurhayatin (Jurnal AGRISEP, 2004)
This research  aims  to analyses  factors  influence  on production  and  resources  allocation  of soybeans  by farmer  at  West Lombok.  Production  function  was estimated  from survey data and technical  efficiency  was used to indicate  farm management  level  through maximum  likelihood,  which  was transformed  into frontier stochastic  production  function.  The land  size,  fertilizer  (urea and  TSP), labor  and pesticide  influence  the production  of soybean  at site.  The technical efficciency  level of Soybean fann was 95,6 percent   The  usage of TSP and pesticide reached allocative efficiency while urea and seeds were al/ocative efficiency yet